The Economics of Agribusiness in Developing Countries: Areas of Opportunities for a New Development Paradigm in the Soybean Supply Chain in Brazil - Medina, Gabriel da Silva (Frontiers in Sustainable Food Systems, 2022)
By understanding the economics of agribusiness, an important economic sector for developing countries, this article explores possibilities for a new development paradigm based on areas of opportunities created for local entrepreneurs. Based on a detailed study of the soybean market chain in Brazil, this paper illustrates that the current neoliberal economic approach has resulted in a business which is dependent on foreign multinationals. While foreign companies hold 60% of the soybean market share, Brazilian groups hold only 40% of the entire business, with the domestic market share concentrated in land (13.3%) and labour (14.3%). But the expansion of foreign investments in agribusiness in the country offers opportunities occupied by Brazilian companies, characterising a situation of associated dependent development. Currently, 12.4% of the share held by Brazilian companies belongs to capital and technology intensive segments such as seed production (2.4%), fertilisers (4.8%), agrochemicals (0.6%), machinery (0.3%), and agro-industry trade (4.3%). The increase in the participation of Brazilian groups in agribusiness requires agricultural policies that can be inspired by a new development paradigm. Opportunities created by foreign investments can be used by domestic groups to increase their share in agro-industrial sectors. Lessons from the Brazilian case can help other developing countries to explore areas of opportunities for domestic investments in dynamic economic sectors such as agribusiness.